High efficiency of nitric acid controls in alleviating particulate nitrate in livestock and urban areas in South Korea. Issue 2 (18th January 2023) - Kim, Haeri; Park, Junsu; Kim, Seunggi; Pawar, Komal Narayan; Song, Mijung
Abstract : Remarkably, enhanced particulate nitrate (NO3 − ) concentrations occur in many environments during particulate matter (PM) pollution; however, information on the formation mechanism and alleviation strategies is still limited. Abstract : Remarkably, enhanced particulate nitrate (NO3 − ) concentrations occur in many environments during particulate matter (PM) pollution; however, information on the formation mechanism and alleviation strategies is still limited. Herein, to explore the NO3 − formation mechanism and conditions, we measured the concentrations of water-soluble inorganic ions in PM1.0 as well as the inorganic gas concentrations of HNO3, NO2, and NH3 in Gimje, a highly dense livestock area, from June to July 2020 and January to February 2021. At the monitoring site, extremely high atmospheric NH3 was measured with an hourly average of 96.9 ± 48.1 ppb, and the daily average of HNO3 and PM1.0 was 0.7 ± 0.7 ppb, and 20.1 ± 8.8 μg m −3, respectively. A clear increase in the NO3 − concentration in PM1.0 was observed on high pollution days (PM1.0 ≥ 20 μg m −3 ), suggesting that HNO3 and NH3 contributed to NO3 − formation. Moreover, we applied the thermodynamic model ISORROPIA-II to predict the NO3 − response to the reduction of total HNO3 (TN), total NH3 (TA), and SO4 2− . The results showed that controlling TN could be more effective in alleviating particulate NO3 − than controlling SO4 2− and TA in the livestock area. We also compared this result to that of a nearby urban area, Jeonju. A similar result was observed, with efficient HNO3 control, which reduced the NO3 − concentration in Jeonju. These measurements and simulations indicated that NO x control could be the most effective approach to reduce particulate NO3 − concentrations in both livestock and urban areas. Our results provide a significant contribution to developing a strategy for alleviating particulate NO3 − pollution.